A representação do trágico em La vida es sueño, de Pedro Calderón de La Barca - Rodrigues, Grygena dos Santos Targino (2015)
This work analyses the representation of the tragic in Pedro Calderon de La Barca s Life is a dream, written in Spain in the 17th century. Searching for the elements which constitute the basis for the dramatic art in the author s historical context, we started by a systematic analysis of the theory of drama, using Aristotle s Poetics and Horace s The Art of Poetry. In doing so, we have reviewed the discussions about basic terms, recollected by theatre and drama studies. These discussions are focused, among other categories, on the elements which compose the tragic action, as well as on the concepts of mimesis and katharsis. The choice of this subject and interest in developing the research came from the study of various Western theories, such as the ones from Aristotle, Horace, Hegel and Szondi, to name a few. Those concepts also served as our initial parameter to the historical contextualization of the dramatic genre, since Calderon de la Barca s play is defined as a baroque tragedy which maintains, in its form, elements from Greek tragedy. This way, we also discuss dramatic modernity, using, mainly, Hegel s considerations, which deal with the dialectical aspect of the dramatic conflict and problematizes the differences between Greek and modern tragic conflicts. Moreover, we proceeded to the analysis of the main characteristics of the so-called Spanish Golden Age, which comprehended 16th, 17th and 18th centuries, proposing reflections about baroque literature and culture. To achieve this purpose, we have gathered contributions from various writers, such as Maravall, Regalado, Morón and Benjamim. By accomplishing this analysis, we intended not only to emphasize the historical and literary background of the play, but also to highlight its philosophical aspect.